Chemical modifications of activated carbons prepared from different Ganoderma residues, their adsorption, and catalytic application - Chen, Bo Jie; Liu, Yang; Liu, Bai Cheng; Huang, Rong Bing; Wu, Pei Ling; Jiang, Tiemin; Dong, Xinhong; Li, Xia; Khoo, Hock Eng; Lee, Say Wah (Matéria, 2024)
ABSTRACT This study aimed to prepare Ganoderma-based activated carbons for chemical adsorption and catalyzing N-(phosphonomethyl)iminodiacetic acid to glyphosate. The activated carbons were prepared by applying different activation conditions. These carbon samples were applied to catalyze N-(phosphonomethyl)iminodiacetic acid to glyphosate. The results showed that the black Ganoderma char activated at 800 °C for 90 min using 40% phosphoric acid had the highest methylene blue adsorption capacity and DPPH scavenging activities, but the methylene blue adsorption capacity of the black Ganoderma sample activated at 800 °C for 90 min using 40% acid-base solution was lower than the red AC sample. These carbon samples had high thermal stability. Chemical modifications of these chars with the carbon modifiers at an optimized activation condition increased the Langmuir-specific surface areas of these carbon samples up to 2055.09 m2/g. The carbon sample of black Ganoderma activated using the 40% acid-base solution at 800 °C for 90 min and coupled with the addition of hydrogen peroxide during ultrasonication and microwave-assisted reactions had the highest glyphosate catalyzing rate. The glyphosate yield obtained from the catalyzing at atmospheric pressure was 58.78 ± 0.28%. These Ganoderma-based activated carbons can replace other carbon materials for catalysis applications and as adsorbents in food and pharmaceutical industries.